2015
DOI: 10.1111/ffe.12328
|View full text |Cite
|
Sign up to set email alerts
|

Design rules for autofrettage of an aluminium valve body

Abstract: The following paper is intended to improve the fatigue behaviour of a complex aluminium valve geometry under high internal cyclic pressure loading. The autofrettage process helps to increase the fatigue durability and a simple but efficient design method for this process is pointed out. Based on non-linear material's behaviour, finite element simulations of the crack-free geometry help to determine the minimum and maximum autofrettage pressure to be used, without iterative crack simulations, which would requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 23 publications
3
10
0
Order By: Relevance
“…These initial cracks were arrested during propagation due to a barrier of compressive residual stresses induced by autofrettage. Similar crack arrest effects were also observed in studies of diesel‐engine injection tubes . Accurate determination of crack propagation time in the presence of these phenomena requires application of fracture mechanics methods.…”
Section: Introductionsupporting
confidence: 63%
“…These initial cracks were arrested during propagation due to a barrier of compressive residual stresses induced by autofrettage. Similar crack arrest effects were also observed in studies of diesel‐engine injection tubes . Accurate determination of crack propagation time in the presence of these phenomena requires application of fracture mechanics methods.…”
Section: Introductionsupporting
confidence: 63%
“…A complete plasticity model and the superposition method for crack propagation did not show any significant difference in the calculated results, which were verified by experiments. Sellen et al 19 showed how the autofrettage process of an aluminium (EN AW 6082 T6) valve body can improve the fatigue life of a 90°‐bore intersection. This design methodology is applied and tested in these experiments.…”
Section: State Of the Artmentioning
confidence: 99%
“…Using linear fracture mechanics, Greuling et al 8,21 and Schön and Seeger 5 described the crack closure effect, and Sellen et al 19 used it to define the crack growth limit of an aluminium component. In linear elastic fracture mechanics, macroscopic crack growth is not given under cyclic load if the effective cyclic threshold stress intensity range Δ K eff is equal or less than the theoretical threshold stress intensity range Δ K th .…”
Section: State Of the Artmentioning
confidence: 99%
“…The study has shown the new method of the estimation of the optimum autofrettage pressure for geometrically complex parts. The procedure is less sensitive for a biassed assessment, as presented by the author [10]. The method can be automated, as shown in the presented example of ANSYS Workbench and nCode.…”
Section: Discussionmentioning
confidence: 94%
“…A recent study [10] has been conducted using the nonlinear finite element method for the automotive hydrogen valve, and the author used iterative method for estimation of the autofrettage pressure for an aluminum valve body.…”
Section: Review Of Literaturementioning
confidence: 99%